2018
DOI: 10.1111/jocn.14328
|View full text |Cite
|
Sign up to set email alerts
|

The older patient's experience of the healthcare chain and information when undergoing colorectal cancer surgery according to the enhanced recovery after surgery concept

Abstract: Patient information must be personalised and made understandable. This can improve self-preparation and participation in the own recovery. Special needs must be addressed early and followed up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(91 citation statements)
references
References 27 publications
2
89
0
Order By: Relevance
“…Lack of trust can lead to non-adherence to prescribed therapies [13,25] because the patients either do not understand what to do, or feel that the information received is not trustworthy. The importance of a good relationship with the patient that enables HPs to build trust and adapt to the patient's information processing ability in complex situations has been highlighted in earlier studies [2,13,16,18,19,21,25].…”
Section: General Discussion and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lack of trust can lead to non-adherence to prescribed therapies [13,25] because the patients either do not understand what to do, or feel that the information received is not trustworthy. The importance of a good relationship with the patient that enables HPs to build trust and adapt to the patient's information processing ability in complex situations has been highlighted in earlier studies [2,13,16,18,19,21,25].…”
Section: General Discussion and Resultsmentioning
confidence: 99%
“…Evidence indicates that good quality information provided in a way that the patient can understand has a number of positive effects for her/him [12,16,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was divided into 3 categories consisting of (1) using the information to make daily life work, Experiences of colorectal cancer patients a recurrent symptom, and patients still needed to sleep a lot and did not have much stamina for up to one month after leaving. This left them unable to carry out common tasks like housework or even their daily routines [18]. Three studies reported that when returning home, some patients intended to perform daily activities or exercise on their own.…”
Section: Theme 1: Sufferingmentioning
confidence: 99%